Bladder stones after bladder augmentation are not what they seem. Issue 2 (April 2016) - Szymanski, Konrad M.; Misseri, Rosalia; Whittam, Benjamin; Lingeman, James E.; Amstutz, Sable; Ring, Joshua D.; Kaefer, Martin; Rink, Richard C.; Cain, Mark P.
Summary: Introduction: Bladder and renal calculi after bladder augmentation are thought to be primarily infectious, yet few studies have reported stone composition. Objective: The primary aim was to assess bladder stone composition after augmentation, and renal stone composition in those with subsequent nephrolithiasis. The exploratory secondary aim was to screen for possible risk factors for developing infectious stones. Study design: Patients treated for bladder stones after bladder augmentation at the present institution between 1981 and 2012 were retrospectively reviewed. Data were collected on demographics, surgeries and stone composition. Patients without stone analysis were excluded. Stones containing struvite, carbonate apatite or ammonium acid ureate were classified as infectious. The following variables were analyzed for a possible association with infectious bladder stone composition: gender, history of cloacal exstrophy, ambulatory status, nephrolithiasis, recurrent urea-splitting urinary tract infections, first vs recurrent stones, timing of presentation with a calculus, history of bladder neck procedures, catheterizable channel and vesicoureteral reflux. Fisher's exact test was used for analysis. Results: Of the 107 patients with bladder stones after bladder augmentation, 85 met inclusion criteria. Median age at augmentation was 8.0 years (follow-up 10.8 years). Forty-four patients (51.8%) recurred (14 multiple recurrences, 143 bladder stones). Renal calculi developed in 19 (22.4%) patients with a bladder stone, and 10 (52.6%) recurred (30 renal stones). Overall, 30.8% of bladder stones were non-infectious (Table). Among patients recurring after an infectious bladder stone, 30.4% recurred with a non-infectious one. Among patients recurring after a non-infectious stone, 84.6% recurred with a non-infectious one ( P = 0.005). Compared with bladder stones, renal stones were more likely to be non-infectious (60.0%, P = 0.003). Of patients with recurrent renal calculi after an infectious stone, 40.0% recurred with a non-infectious one. No clinical variables were significantly associated with infectious stone composition on univariate (≥0.28) or bivariate analysis (≥0.36). Discussion: This study had several limitations: it was not possible to accurately assess adherence with bladder irrigations, and routine metabolic evaluations were not performed. The findings may not apply to patients in all clinical settings. While stone analysis was available for 3/4 of the stones, similar rates of incomplete stone analyses have been reported in other series. Conclusions: In patients with bladder augmentation, 1/3 of bladder stones and >1/2 of renal stones were non-infectious. Furthermore, an infectious stone does not imply an infectious recurrent stone and no known clinical variables appear to be associated with stone composition, suggesting that there is a possible metabolic component in stone formation after bladder augmentation. Table Stone composition of bladder and renal stones in patients with augmented bladders. Stone composition Bladder stones (n = 143) (%) Renal stones (n = 30) (%) Infectious stones 99 (69.2%) 12 (40.0%) Struvite 79 (55.2%) 11 (36.7%) Pure carbonate apatite 15 (10.5%) 1 (3.3%) Pure ammonium acid ureate 2 (1.4%) 0 (0.0%) Mixed stones with calcium phosphate 4 (2.8%) 0 (0.0%) Non-infectious stones 44 (30.8%) 18 (60.0%) Calcium phosphate 41 (28.7%) 14 (46.7%) Pure calcium oxalate 0 (0.0%) 4 (13.3%) Uric acid 3 (2.1%) 0 (0.0%)